Synthesis and Dyeing Performance of Disperse Dyes Based on 4-Hydroxy-1-Methyl-Quinolin-2(1H)-One System - Mehta, H.T.; Mehta, A.G. (Asian Journal of Chemistry, 2010)
4-Hydroxy-1-methyl-quinolin-2( 1H)-one (III) used as a coupling component, was prepared by the methylation of anthranilic acid giving N-methylanthranilic acid (I) followed by acetylation giving N-methyl-N- acetyl anthranilic acid (II) and ring closure. Twenty 3-arylazo-4- hydroxy-1-methyl-quinolin-2( 1H)-ones disperse dyes (Va-t) were prepared by coupling(lII) with various diazo components (lVa-t). The compounds Va-t are characterized by elemental and spectral analyses and their dyeing performance on polyester fibre was assessed. These compounds gave yellow. orange, brown and red shades with poor to good light-fastness, very good to excellent wash fastness and poor to excellent exhaustion.